2017
DOI: 10.1111/iwj.12748
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of a novel, hypothermically stored amniotic membrane for use in a chronic wound environment

Abstract: Chronic wounds require extensive healing time and place patients at risk of infection and amputation. Recently, a fresh hypothermically stored amniotic membrane (HSAM) was developed and has subsequently shown promise in its ability to effectively heal chronic wounds. The purpose of this study is to investigate the mechanisms of action that contribute to wound-healing responses observed with HSAM. A proteomic analysis was conducted on HSAM, measuring 25 growth factors specific to wound healing within the grafts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 81 publications
3
51
0
Order By: Relevance
“…Proteomic analysis of dACM was conducted as described in detail elsewhere . Briefly, a custom quantitative multiplex enzyme‐linked immunosorbent assay (ELISA) proteomics microarray (Raybiotech Inc, Norcross, Georgia) was used to quantify growth factors and cytokines within dACM.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Proteomic analysis of dACM was conducted as described in detail elsewhere . Briefly, a custom quantitative multiplex enzyme‐linked immunosorbent assay (ELISA) proteomics microarray (Raybiotech Inc, Norcross, Georgia) was used to quantify growth factors and cytokines within dACM.…”
Section: Methodsmentioning
confidence: 99%
“…Cell proliferation experiments were conducted as previously described in detail . Briefly, fibroblasts and keratinocytes were cultured with 50%, 25%, and 10% (vol/vol) dACM CM for 14 days (fibroblasts) or 10 days (keratinocytes) under standard conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Placental‐derived tissues have been shown to support repair of several tissue types, including bone, tendon, and skin . They also have known angiogenic properties, often attributed to the presence of angiogenic growth factors within the matrix . Although numerous studies have shown angiogenic properties of placental tissues in a variety of models, relatively little work has been done to characterize the potential mechanisms through which these tissues may promote angiogenesis.…”
Section: Introductionmentioning
confidence: 99%